Two-Year Change in Blood Pressure Status and Left Ventricular Mass Index in Chinese Children - Li, Zilin; Duan, Yao; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Medicine, 2021)
Background: Elevated blood pressure (BP) is associated with target organ damage, such as left ventricular hypertrophy (LVH), in childhood. However, it is unclear if children who resolve elevated BP have reduced levels of left ventricular mass index (LVMI). This study aimed to examine the association between change in BP status over 2 years and LVMI among Chinese children. Methods: Data were from 1183 children aged 6-11 years at baseline in 2017 who were followed-up in 2019 in the Huantai Childhood Cardiovascular Health Cohort Study. Change in BP status over 2 years from baseline to follow-up was categorized as: persistent normal BP, resolved elevated BP (elevated BP at baseline, normal BP at follow-up), incident elevated BP (normal BP at baseline, elevated BP at follow-up), and persistent elevated BP. Elevated BP status was defined according to National reference standards as systolic or diastolic BP levels ≥sex-, age-, and height-specific 95th percentiles. Results: LVMI levels were lowest in children with persistent normal BP (30.13 g/m2.7), higher in those with incident elevated BP (31.27 g/m2.7), and highest in those with persistent elevated BP (33.26 g/m2.7). However, LVMI levels in those who had resolved elevated BP (30.67 g/m2.7) were similar to those with persistent normal BP. In the fully adjusted model, compared with children with persistent normal BP, those with persistent elevated BP and incident elevated BP had higher LVMI at follow-up (ß=3.131, P<0.001; ß=1.143, P=0.041, respectively). In contrast, those who had resolved elevated BP did not have a significantly higher LVMI (ß=0.545, P=0.194) than those with persistent normal BP. Conclusion: Developing or maintaining elevated BP over a 2-year period in childhood associated with higher levels of LVMI, but those able to resolve their elevated BP status over the same period had LVMI levels that were similar with those who had normal BP at both time-points. Thus, it is important to identify children with elevated BP at early time, and to take effective measures to lower their BP levels, thereby reducing high LVMI levels and related cardiovascular diseases in future.